2020
DOI: 10.29309/tpmj/2020.27.03.3156
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and morphology of benign histopathological lesions in total abdominal hysterectomy specimens.

Abstract: Hysterectomy is one of the most frequently performed gynecological procedure all over the globe undertaken for varying indications, to effectively cure many gynaecological conditions. Histopathological analysis of the hysterectomy specimens should be undertaken for justification of procedure and diagnostic purposes. Objectives: To determine the frequency and morphology of different benign histopathological lesions in total abdominal hysterectomy specimens. Study Design: Descriptive cross-sectional study. Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The present study showed that the most common histopathological diagnosis in uterine corpus samples was leiomyoma (40%), followed by adenomyosis (11%). One previous study from Pakistan reported similar results showing leiomyoma 66% of cases and adenomyosis 21% of cases 20 In a study conducted at Karachi, leiomyoma was 33%, adenomyosis was 23% and combined leiomyoma with adenomyosis was 23. 16 Similar results were shown in studies conducted in Lahore, Tanzania, India, United States and Nepal.…”
Section: Discussionmentioning
confidence: 54%
“…The present study showed that the most common histopathological diagnosis in uterine corpus samples was leiomyoma (40%), followed by adenomyosis (11%). One previous study from Pakistan reported similar results showing leiomyoma 66% of cases and adenomyosis 21% of cases 20 In a study conducted at Karachi, leiomyoma was 33%, adenomyosis was 23% and combined leiomyoma with adenomyosis was 23. 16 Similar results were shown in studies conducted in Lahore, Tanzania, India, United States and Nepal.…”
Section: Discussionmentioning
confidence: 54%
“…The majority of the samples sent for histopathology in our study were from the age group of 31-50 years (71.6%). This range is quite typical for gynecological problems that result in sampling, particularly around the late forties, as observed in several of the other studies referenced [ 3 , 4 , 7 , 8 ]. This is probably due to this being the peak reproductive age and females are more likely to present to a primary physician as compared to other age groups.…”
Section: Discussionmentioning
confidence: 63%
“…Out of 458 uterine samples in our study 24.2% were diagnosed as leiomyoma, followed by 18.8% being adenomyoma. These findings are mirrored by studies conducted in Lahore and Karachi, the highest proportion of diagnosis being leiomyoma in uterine samples, 69% and 66%, respectively [4,7]. The latter also had adenomyosis as the second most common finding at 21%.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations